iPad 2 : portable genius - McFedries, Paul (Portable genius, 2011)
Looks at the features and functions of the iPad2, covering such topics as configuration, Web surfing, email, photos, the eBook library, iTunes, videos, managing contacts, using the Calendar App, and accessing the App Store